2015
DOI: 10.1186/s40200-015-0200-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum uric acid level and metabolic syndrome components

Abstract: BackgroundSerum uric acid levels is reported to be associated with a variety of cardiometabolic risk factors; however, its direct association with metabolic syndrome (MetS) remains controversial. Thus, we examined the association of serum uric acid concentrations with the MetS components.MethodsMetS was defined according to the National Cholesterol Education Program (NCEP) criteria. This case–control study comprised 101 non-smoking individuals (41 in the MetS group and 60 in the non-MetS group). Blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 49 publications
17
61
1
Order By: Relevance
“…Little information on its association with MetS in Chinese population is available. Consistent with the previous finding, Pearson's correlation analyses in this work suggests that hyperuricemia is more correlated with MetS in males than in females (24). Our findings also suggested that UAC and TG could be a risk factor for MetS.…”
Section: Discussionsupporting
confidence: 92%
“…Little information on its association with MetS in Chinese population is available. Consistent with the previous finding, Pearson's correlation analyses in this work suggests that hyperuricemia is more correlated with MetS in males than in females (24). Our findings also suggested that UAC and TG could be a risk factor for MetS.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, our cases showed higher uric acid levels which is in accordance with Nejatinamini et al 37 who reported that uric acid and MS components supports might be an additional components of MS. Uric acid may not only acts as surrogate marker of MS, but also have a pathogenic role in the development of MS, and therapies that lower uric acid may improve certain components of MS 38 . Although hyperuricemia is recognized as a risk factor for obesity, diabetes and MS, the precise physiological mechanisms by which uric acid contribute to these diseases state remain unclear 39 .…”
Section: Discussionsupporting
confidence: 92%
“…Hyperuricemia has been found to be associated with metabolic syndrome (26)(27)(28). It has been emphasized that an increase in uric acid levels that is recognized early can be a sign of metabolic syndrome that may develop (29).…”
Section: Relationship With Metabolic Syndromementioning
confidence: 99%
“…An increased uric acid level is an independent risk factor in metabolic syndrome (34). Nejatinami et al (28) made the interpretation that an increased uric acid level was one of the risk factors of metabolic syndrome in the results of a study that they conducted. They expressed the opinion that hyperuricemia should be included as an additional component of metabolic syndrome.…”
Section: Relationship With Metabolic Syndromementioning
confidence: 99%